To describe an alien planet: An experience of landscape in "The Voyage of the Beagle" by Charles Darwin - Schollenberger, Justyna (Polskie Studia Krajobrazowe, 2019)
This text presents an attempt to reread Darwin’s account of his journey on the Beagle. That account constitutes a report of meetings and confrontations with various “strangers”: men, animals, as well as with different faces of otherness and exoticism, that culminate in a landscape so radically distinct from the European one, namely that of the South Pacific. This interpretation allows us to look at Darwin—the narrator—as more than just a naive traveler who observes and judges the world exclusively through the narrow perspective of British imperialism. The naturalist struggles with describing that which exceeds his previous experiences. The imperialistic perspective of landscape taken up in this text allows us to reflect on Darwin’s perception of the landscape. The sights analyzed in the text are foremost treated as emanations of the powers of nature. At the same time, Darwin defines these sights in categories that are not scientific but aesthetic, finding them beautiful and sublime.